Peculiar Verbal System in Jaﬀna Tamil - Subathini, R. (Tamil University, Thanjavur, 2024)
The Jaﬀna Tamil variety, which is found in the northern region of Sri Lanka—speciﬁcally, the Jaﬀna peninsula—is widely regarded as the most “characteristic” of all Sri Lankan Tamil dialects. Jaﬀna Tamil has evolved as an own personality because it has been suﬃciently separated from Indian variety of the language. A variety of verbal system characteristics contribute to this unique character. Thus, this analysis can be seen as an initial attempt to identify and characterize a unique feature of the Jaﬀna Tamil verbal system. The following characteristic is speciﬁc to the Jaﬀna dialect, even though certain individual features may be shared by others. The creation of a subsystem of ﬁnite, agreement of verb forms based on the present and past tense of the verbal adjective for combined with the personal pronouns (sometimes called the relative participle). While similar sequences might exist in other languages, they don’t, as far as we know, form a ﬁnite subsystem with the same purposes as those in Jaﬀna Tamil. Pronominal verbs have present and past tenses, and each has an associated negative. Utilizing a hybrid approach, this work aims to investigate ﬁnite verb systems with instances that can be used in verbal adjectives, question forms, negative forms, and pronominal verbs. Finally, the analysis explored with examples of these unusual characteristics using spoken forms of Jaﬀna Tamil.
Keywords: Jaﬀna Tamil; Verbal system; Finite sub system; Pronominal verb forms; Negative forms